PENGARUH CAPITAL ADEQUACY RATIO (CAR), QUICK RATIO, RASIO BIAYA OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL (BOPO) TERHADAP RETURN ON EQUITY (ROE) PADA BANK KONVENSIONAL DI INDONESIA PERIODE 2010 - 2014 - Hendrawati Hendrawati (Jurnal Manajemen FE-UB, 2018)
This study aims to examine the effect of Capital Adequacy Ratio (CAR), Quick Ratio, Operational Cost Ratio on Operating Income (BOPO), and the Non-Performing Loan (NPL) ratio to Return on Equity (ROE) partially and simultaneously. The type of research used is associative research. The method used in this study is panel data estimation method, simple linear regression, and multiple linear regression. The data sources used in this study are secondary data in the form of financial statements of 10 conventional banks obtained from 2010 to 2014. The samples in this study were 10 conventional banks. The sampling technique in this study was purposive sampling where samples were taken based on the reasons for clear criteria. The data analysis technique used in this study is panel data estimation method, simple linear regression, and multiple linear regression. To test the significance of the regression coefficient using the t-test and F-test with significance (sig) of 5%. Processing data using Eviews 09.00. The results of this study indicate that the Capital Adequacy Ratio (CAR), Quick Ratio, Operational Cost Ratio to Return on Equity (ROE) because of Fcount> Ftable (5.42E + 27> 2.45) and Fstatistic significance value (Fcount) <0.05 (0.000000 <0.05). The results of this study also show that Capital Adequacy Ratio (CAR) has a partially significant effect on Return on Equity (ROE), Quick Ratio has a partially significant effect on Return on Equity (ROE), Operational Cost Ratio to Return on Equity (ROE), and The Non Performing Loan (NPL) ratio has a partially significant effect on Return on Equity (ROE) where the tstatistic significance value (tcount) for each of the independent variables is <0.05 (0.0000 <0.05).